(untitled) (Research, Society and Development, 2020)
This study aimed to investigate the contributions of Digital Information and Communication Technologies in the teaching and learning of Mathematics. The data collection instrument used was an online questionnaire, applied to 67 teachers. The research results show that technologies contribute to the teaching and learning process of Mathematics, helping to visualize information, build knowledge and motivate. However, it needs a more careful look with regard to public policies, so that teachers receive adequate training and, that schools and institutions obtain assistance for the maintenance of their laboratories, as well as a better internet signal.